2021
DOI: 10.1111/cote.12543
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of textile wastewater treated by moving bed biofilm reactor coupled with membrane bioreactor

Abstract: A laboratory‐scale pilot plant of moving bed biofilm reactor coupled with membrane bioreactor (MBBR‐MBR) was studied with regard to wastewater treatment in the textile industry, and the reuse feasibility of treated water was investigated. The pilot plant comprised two connected parts: an aerobic tank filled with carriers and a submerged membrane tank. The MBBR‐MBR system reduced the hydraulic retention time to 1 day, which is very promising compared with conventional biological treatment in the textile industr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…In a previous study, a Moving Bed Biofilm Reactor (MBBR), loaded with bio carriers that contained zinc nanoparticles, and the filling ratio was set at 40 %, was employed for the treatment of textile wastewater that showed a COD removal efficiency of 70 % [ 26 ]. A similar result (93 % COD removal) to this study was reported by Yang et al (2021) [ 27 ]. They used an AnMBBR-AeMBR treatment method.…”
Section: Resultssupporting
confidence: 92%
“…In a previous study, a Moving Bed Biofilm Reactor (MBBR), loaded with bio carriers that contained zinc nanoparticles, and the filling ratio was set at 40 %, was employed for the treatment of textile wastewater that showed a COD removal efficiency of 70 % [ 26 ]. A similar result (93 % COD removal) to this study was reported by Yang et al (2021) [ 27 ]. They used an AnMBBR-AeMBR treatment method.…”
Section: Resultssupporting
confidence: 92%
“…The engineered LCC1-62 was produced in the recombinant P. pastoris, and the partially purified laccase was used for the treatment of real textile effluent in an EMR. The membrane-based technologies have shown superior performance in the treatment of domestic wastewater and a wide range of effluents from several industries (Jegatheesan et al, 2016;Al-Asheh et al, 2021;Yang et al, 2021). For instance, ∼80% removal of Remazol Brilliant Blue R was achieved in an EMR using laccase from Trametes versicolor with the aid of syringaldehyde (Mendoza et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The anaerobic bioreactor joins the sedimentation of solids and their deposit in the base, with the floating material of the WWTP and the suspended active biomass. Both bottom mud and floating material provide adequate space for microbial growth [77,79] This type of bioreactor generates sludge and microbial biomass as residual products which are treated for reuse before leaving [80,81]. This method has indicated good efficiency in eliminating drugs of abuse at low concentrations, but in recent studies it has been accompanied by chlorination and maturation in ponds in order to allow better removal of drugs of abuse and their metabolites from WWTP [77,82,83].…”
Section: Mixed-flow Bioreactormentioning
confidence: 99%